The Impact of Higher Oil Prices on Low Income Countries and on the Poor - World Bank (Washington, DC, 2014)
The rapid and large oil price rise experienced during 2004 has created widespread concern about its impact on low income countries and on poor households in many countries. To appreciate the magnitude of this impact and to formulate policies to ameliorate these effects, a number of questions need to be answered. What are the routes by which countries are impacted? Which countries are most vulnerable to oil shocks? What determines the degree of vulnerability to such shocks? How much are the poor in various countries impacted by the effects of higher oil prices? What policies can reduce the vulnerability of countries to oil shocks, both immediately and in the medium to long run? Three levels of analysis are used to discuss these issues: the macroeconomic, that looks at the direct impact of the balance of payments and the necessary adjustment of GDP to restore equilibrium; the mesoeconomic, that looks at factors which determine a country's propensity to be a net oil importers, including oil self-sufficiency, oil dependence and energy intensity; and the microeconomic that looks at the direct impact and indirect impacts on households of an increase in oil prices.